Oxidative stress accelerates intestinal tumorigenesis by enhancing 8-oxoguanine-mediated mutagenesis in MUTYH-deficient mice - Ohno, Mizuki; Takano, Noriko; Hidaka, Kyoko; Sasaki, Fumiko; Yamauchi, Kazumi; Aoki, Yasunobu; Nohmi, Takehiko; Nakabeppu, Yusaku; Nakatsu, Yoshimichi; Tsuzuki, Teruhisa (Genome Research, 2024)
Oxidative stress–induced DNA damage and its repair systems are related to cancer etiology; however, the molecular basis triggering tumorigenesis is not well understood. Here, we aimed to explore the causal relationship between oxidative stress, somatic mutations in pre-tumor-initiated normal tissues, and tumor incidence in the small intestines of MUTYH-proficient and MUTYH-deficient mice. MUTYH is a base excision repair enzyme associated with human colorectal cancer. Mice were administered different concentrations of potassium bromate (KBrO3; an oxidizing agent)–containing water for 4 wk for mutagenesis studies or 16 wk for tumorigenesis studies. All Mutyh−/− mice treated with >0.1% KBrO3 developed multiple tumors, and the average tumor number increased dose dependently. Somatic mutation analysis of Mutyh−/−/rpsL transgenic mice revealed that G:C  > T:A transversion was the only mutation type correlated positively with KBrO3 dose and tumor incidence. These mutations preferentially occurred at 5′G in GG and GAA sequences in rpsL. This characteristic mutation pattern was also observed in the genomic region of Mutyh−/− tumors using whole-exome sequencing. It closely corresponded to signature 18 and SBS36, typically caused by 8-oxo-guanine (8-oxoG). 8-oxoG-induced mutations were sequence context dependent, yielding a biased amino acid change leading to missense and stop-gain mutations. These mutations frequently occurred in critical amino acid codons of known cancer drivers, Apc or Ctnnb1, known for activating Wnt signal pathway. Our results indicate that oxidative stress contributes to increased tumor incidence by elevating the likelihood of gaining driver mutations by increasing 8-oxoG-mediated mutagenesis, particularly under MUTYH-deficient conditions.